A thermal latent imidazole complex containing copper (II) as the curing agent for an epoxy-based glass fiber composite. Issue 11 (June 2022) - Yang, Bo; Wei, Yi; Liu, Yanbo; Qiu, Yiping
Epoxy-based glass fiber composites are widely used in various fields, such as automotive, marine, and aircraft, owing to their high strength and light weight compared to traditional metal materials. However, the epoxy-based resins or prepregs cannot be stored for a long time at room temperature owing to their high reactivity. In this study, 1-cyanoethyl-2-ethyl-4-methylimidazole (CEMI) is a complex with copper chloride to improve its thermal latency towards epoxy resins, and the epoxy-based glass fiber composite is made by prepreg processing. The composition of the imidazole–copper (II) complex (Complex-S) is characterized by elemental analysis and inductively coupled plasma optical emission spectrometry. Thermal dissociation of Complex-S is conducted by differential scanning calorimetry and Fourier transform infrared spectroscopy. With Complex-S as a latent curing agent, the thermal and mechanical properties of epoxy resins are studied. The epoxy systems show distinctly prolonged shelf life at room temperature. Moreover, the composite with Complex-S has a higher flexure strength and modulus comparable to that with CEMI.